Harnessing tissue-specific genome editing in plants through CRISPR/Cas system: current state and future prospects - Singha, Dhanawantari L.; Das, Debajit; Sarki, Yogita N.; Chowdhury, Naimisha; Sharma, Monica; Maharana, Jitendra; Chikkaputtaiah, Channakeshavaiah (Planta, 2022)
Main conclusion In a nutshell, tissue-specific CRISPR/Cas genome editing is the most promising approach for crop improvement which can bypass the hurdle associated with constitutive GE such as off target and pleotropic effects for targeted crop improvement. CRISPR/Cas is a powerful genome-editing tool with a wide range of applications for the genetic improvement of crops. However, the constitutive genome editing of vital genes is often associated with pleiotropic effects on other genes, needless metabolic burden, or interference in the cellular machinery. Tissue-specific genome editing (TSGE), on the other hand, enables researchers to study those genes in specific cells, tissues, or organs without disturbing neighboring groups of cells. Until recently, there was only limited proof of the TSGE concept, where the CRISPR-TSKO tool was successfully used in Arabidopsis , tomato, and cotton, laying a solid foundation for crop improvement. In this review, we have laid out valuable insights into the concept and application of TSGE on relatively unexplored areas such as grain trait improvement under favorable or unfavorable conditions. We also enlisted some of the prominent tissue-specific promoters and described the procedure of their isolation with several TSGE promoter expression systems in detail. Moreover, we highlighted potential negative regulatory genes that could be targeted through TSGE using tissue-specific promoters. In a nutshell, tissue-specific CRISPR/Cas genome editing is the most promising approach for crop improvement which can bypass the hurdle associated with constitutive GE such as off target and pleotropic effects for targeted crop improvement.